2016
DOI: 10.5815/ijmecs.2016.07.01
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of MySQL Workbench in Teaching Entity-Relationship Diagram (ERD) to Relational Schema Mapping

Abstract: Abstract-While designing a database at the conceptual level using the Entity-Relationship (ER) model is challenging for novices, mapping an Entity-Relationship Diagram (ERD) to a relational schema is not an easy task, either. One of the problems is students' lack of understanding of the underlying mapping principles. The mental gap between the two models in students also makes it difficult for them to perform the conversion. This paper describes two studies that aimed at helping students fill the gap and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Yang and Cao, [25] investigated how MySQL Workbench ̶ a visual tool for data modelling ̶ can be used for helping students improve their performance in the ER model to RDS transformation. They also investigated the effects of using MySQL Workbench, in teaching ER to relational transformation.…”
Section: B Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang and Cao, [25] investigated how MySQL Workbench ̶ a visual tool for data modelling ̶ can be used for helping students improve their performance in the ER model to RDS transformation. They also investigated the effects of using MySQL Workbench, in teaching ER to relational transformation.…”
Section: B Related Researchmentioning
confidence: 99%
“…They also investigated the effects of using MySQL Workbench, in teaching ER to relational transformation. The authors found that visualization of the transformation process could increase the students' interest in it and their engagement with it, as well as their ability to transform the ER model's concepts to the RDS [25]. Wu et al [26] investigated several versions of the ER model to understand the right ER diagram convention used to teach ER modelling to undergraduate students.…”
Section: B Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the diagram is designed, it is then converted into a relational schema before the actual database is created and implemented. However, although it may sound easy to map an ER diagram, it is not an easy task to perform, it is not as easy for a novice, as it needs to meet some requirements and it involves complex logical thinking [21].…”
Section: Entity-relationship Diagrammentioning
confidence: 99%